Beliefs and Rituals - Grbić, Jadranka (2000)
This contribution deals with the remains of the early forms of the Croatian religiosity: with the ideas, beliefs and rituals, also including the phenomena tightly connected with all aspects of life: starting from customs and moral norms of a community and the social relationships, through dwelling, economy, nourishment and dressing to the artistic expression.
Projekt MZOS
ENG